Nitrogen and phosphorous adsorption from post-hydrothermal liquefaction wastewater using three types of zeolites - Xia, Ran; Na, Duan; Zhang, Yuanhui; Baoming, Li; Zhidan, Liu; Haifeng, Lu (International Journal of Agricultural and Biological Engineering, 2015)
Hydrothermal liquefaction (HTL) has been studied as a promising technology for converting wet biomass into bio-crude oil and the nutrient-rich post-hydrothermal liquefaction wastewater (PHWW) could be reused for algae and bacteria production. However, the PHWW from HTL contains various types of contaminants that need to be removed before reuse. Too high nutrients (nitrogen and phosphorous) contents, such as ammonium, are inhibitive to algal growth and bacteria species in anaerobic process. It is desirable to reduce nutrients concentration in PHWW to an acceptable level using zeolite adsorption. This study investigated nitrogen and phosphorous adsorption efficiencies from PHWW using three types of zeolites: activated clinoptilolite, natural clinoptilolite and Na-modified zeolite. Effects of ions and pH in the adsorption process were also investigated. Results showed that three zeolite variables affecting ammonium adsorption process could be ranked as follows: zeolite dosage > type > particle size, via an orthogonal experiment design. Activated clinoptilolite, with a particle size of 0.18-0.30 mm and a dosage of 0.4 g/mL demonstrated the highest ammonium adsorption efficiency of 54.92%. Zeolite could also adsorb organic nitrogen and had a high adsorption efficiency of phosphorous (97.85%). This study showed that zeolite is effective to adsorb nutrients in PHWW. The adsorption treated PHWW can then be used for culturing algae or anaerobic treatment, and the adsorbed nutrients can be reused later.Keywords: adsorption, ammonium, nutrients; phosphorous, zeolite, post-hydrothermal liquefaction wastewater (PHWW)DOI: 10.3965/j.ijabe.20150805.1561Citation: Ran X, Duan N, Zhang Y H, Li B M, Liu Z D, Lu H F. Nitrogen and phosphorous adsorption from post-hydrothermal liquefaction wastewater using three types of zeolites. Int J Agric & Biol Eng, 2015; 8(5): 86－95.